1964
DOI: 10.1002/ar.1091500305
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of pressures across the elbow joint

Abstract: To ascertain the pathway (s) along which forces are conducted from the hand to the humerus in the human cadaver specially designed pressure sensitive transducers were introduced into the radio-capitular and ulnar-trochlear components of the elbow joint. A constant force was applied to the hand, and changes in electrical resistance and hence pressure across the elbow joint where recorded. It was observed that 57% of the force applied crossed the radio-capitular joint while 43% crossed the ulnar-trochlear joint.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(80 citation statements)
references
References 1 publication
2
72
0
6
Order By: Relevance
“…Therefore, the mechanical performance of the plating configuration was assessed in the most relevant physiological loading condition of the elbow joint [3]. Loads were physiologically distributed on the elbow joint [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the mechanical performance of the plating configuration was assessed in the most relevant physiological loading condition of the elbow joint [3]. Loads were physiologically distributed on the elbow joint [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of load application [12,13] as well as testing procedures [14] were based on previous studies and are briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain a clearer understanding of the consequences of radial head resections (1,18,32,59,71,84) (elbow instability, radiocapitellar joint contact loss, proximal migration of the radius) in comminuted radial head fractures, research was carried out on human cadaver elbows in order to examine the function of the radial head (31,51,63,64,66) and the role of the anterior band of the medial collateral ligament (aMCL), the interosseous membrane (MI) and the triangular fibrocartilaginous complex (TFCC) (20,37,38,66,70,74,75).…”
Section: Biomechanicsmentioning
confidence: 99%
“…Basic experimental research showed that 60% of an axial load at the elbow is transmitted through the radiocapitellar (RC) joint (3,31,64), especially in pronation between 0°and 30°flexion (65).…”
Section: Biomechanicsmentioning
confidence: 99%